NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM FILM ANIMASI UPIN IPIN EPISODE ESOK HARI RAYA, GONG XI FA CAI, DAN DEEPAVALI - Heri Cahyono; Yeni Susanti (Universitas Muhammadiyah Metro, 2019)
Multicultural education is education that promotes diversity, difference, and tolerance. The values of multicultural education that are implanted are expected to be a solution to resolve or avoid cases that often occur in Indonesia because of the background of cultural differences in society. The planting of multicultural education values must be applied to the general public, especially to students as early as possible. The values of multicultural education can be done in various ways, one of them is using animated film media, namely the Upin Ipin animated film. children in general will better understand what they often see. Upin Ipin's animated film tomorrow's episodes, gong xi fa cai, and deepavali illustrate how peaceful and peaceful multicultural life. Where in the film illustrates how the reality of multicultural life that lives peacefully even with different cultural backgrounds. In addition, in the animated film Upin Ipin tomorrow's episodes, gong xi fa cai, and deepavali there are multicultural education values namely tolerance, democratic values, help please values, pluralism values, justice values, equality values, equality values, humanism values, and the value puts the dialog first.Keywords: Multicultural Values, Tomorrow's Holiday, Gong Xi Fa Cai, and Deepavali